Reinterpretación cuantitativa de diagrafías geofísicas en el pozo centenera 2 - Rivadeneira, Dennis (2010)
The present project aims to reinterpret the Centenera 2 well logs, being focused mainly in the improvement of the interpretation of porosities and other characteristics present in the formations. In order to complete this objective, it has been developed a methodology that could be applicable to similar studies, especially when old well logs are studied. The methodology begins with a process that consists on transforming the original paper well logs into digital format well logs, so they can be treated by computer. Then, the digitized well logs are corrected for well effects (temperature, diameter, mud density, etc.). Later, a general interpretation of the well is made, subdividing it in several zones geologically different, for this way to choose more economic interest zones. Finally a quantitative interpretation of the formations is carried out, determining their porosities through different methods. The data obtained by the methodology, demonstrated the existence of formations potentially producers of gas, the same ones that have bigger porosities to those described by studies in past decades.